Characterization of the two intracellular lipases of Y. lipolytica encoded by TGL3 and TGL4 genes: New insights into the role of intracellular lipases and lipid body organisation - Dulermo, Thierry; Tréton, Brigitte; Beopoulos, Athanasios; Kabran Gnankon, Affoué Philomène; Haddouche, Ramdane; Nicaud, Jean-Marc (Biochimica et biophysica acta, 2013)
Eukaryotes store lipids in a specialised organelle, the lipid body (LB), mainly as triglycerides (TAGs). Both the rates of synthesis and degradation contribute to the control of the accumulation of TAGs. The synthesis of TAGs in yeasts has been well documented, especially in the model yeast Saccharomyces cerevisiae and in the oleaginous yeast Yarrowia lipolytica. However, descriptions of the processes involved in TAG degradation are more scarce and mostly for S. cerevisiae. Here, we report the characterisation of two Y. lipolytica genes, YlTGL3 and YlTGL4, encoding intracellular lipases involved in TAG degradation. The two proteins are localised in lipid bodies, and YlTgl4 was mainly found at the interface between LBs. Surprisingly, the spatial organisation of YlTgl3 and YlTgl4 depends on the culture medium and on the physiological phase of the cell. Inactivation of one or both genes doubles the lipid accumulation capacity of Y. lipolytica, increasing the cell's capacity to accumulate TAGs. The amino acid sequence of YlTgl4 contains the consensus sequence motif (G/A)XSXG, typical of serine hydrolases, whereas YlTgl3 does not. Single and double mutants are unable to degrade TAGs, and higher expression of YlTgl4 correlates with TAG degradation. Therefore, we propose that YlTgl4 is the main lipase responsible for TAG degradation and that YlTgl3 may act as a positive regulator of YlTgl4 rather than a functional lipase. Thus, contrary to S. cerevisiae, Y. lipolytica possesses two intracellular lipases with distinct roles and with distinct localisations in the LB. •We analysed two intracellular lipases (Tgl3 and Tgl4) of Y. lipolytica.•Inactivation of both lipases increases TAG content and prevent its remobilisation.•Both lipases present different localisations.•Both proteins need each other to be functional.•Possible interaction between both lipases, Tgl3 may act as an activator of Tgl4.